Benzoporphyrins: Selective Co-sensitization in Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa, Ruben Dario; Malig, Jenny; Jux, Norbert; Guldi, Dirk Michael (Chemistry - A European Journal, 2016)
A novel class of dyes, namely benzoporphyrins, was synthesized and implemented into dye-sensitized solar cells. They feature complementary absorptions compared to N719, which renders them promising candidates for co-sensitization in DSSCs. Notably, metallated benzoporphyrins reveal a TiO2-nanoparticle attachment that is size and aggregation dependent. Therefore, unproductive energy-transfer events between the selectively attached dyes can be prevented. In light of the latter, an efficiency improvement of 39 % has been achieved upon selective adsorption of benzoporphyrins and N719 onto different layers of TiO2 photoelectrode.
EAM Import::2019-03-13

Carbon Nanohorn-based electrolyte for Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa Riquelme, Rubén Dario; Casillas Pacheco, Ruben; Kohler, Florian; Wasserscheid, Peter; Prato, Maurizio; Guldi, Dirk Michael (Energy and Environmental Science, 2014)
For the first time, carbon nanohorns were implemented into solid-state electrolytes for highly efficient solid-state and quasi-solid-state DSSCs. They feature an effective catalytic behavior towards the reduction of I3- and enhance the I3- diffusivity into the electrolyte. In a final device, solar cells with 7.84% efficiency at room temperature were achieved. As a matter of fact, this is the highest reported efficiency for nanocarbon-based electrolytes up to date.

Elucidating the electronic properties of single-wall carbon nanohorns - Zieleniewska, Anna; Lodermeyer, Fabian; Prato, Maurizio; Rumbles, Garry; Guldi, Dirk Michael; Blackburn, Jeffrey L. (Journal of Materials Chemistry C, 2022)
Single-walled carbon nanohorns are an allotrope of carbon with promising properties for a variety of applications. Despite their promise, the majority carrier type (i.e. electrons or holes) that defines the electronic properties of this novel semiconductor is poorly understood and so far only indirect measurements have been employed to arrive at contradictory results. Here, we directly determine the majority carrier type in single-wall carbon nanohorns for the first time by means of thermopower measurements. Using this direct method, we show that SWCNH films exhibit a positive Seebeck coefficient indicating that SWCNHs behave as p-type semiconductors. This result is further corroborated by intentionally tuning the hole or electron concentrations of SWCNH layers via redox doping with molecular electron acceptors and donors, respectively. These results provide a framework for both measuring and chemically tuning the majority carrier type in this emerging nanocarbon semiconductor.
CRIS-Team WoS Importer:2022-04-15

Facile and quick preparation of carbon nanohorn-based counter electrodes for efficient dye-sensitized solar cells - Lodermeyer, Fabian; Prato, Maurizio; Costa, Ruben Dario; Guldi, Dirk Michael (Nanoscale, 2016)
For the first time, Pt-free counter electrodes based on carbon nanohorns for highly efficient dye-sensitized solar cells were assembled by a facile and fast drop cast technique. These novel electrodes feature an effective catalytic behavior towards the reduction of I3- and, as such, afford even higher short-circuit current densities compared to Pt-based references. In a final device, solar cells with 7.7% efficiency were achieved.
EAM Import::2019-03-14

Hydrogen bonding mediated orthogonal and reversible self-assembly of porphyrin sensitizers onto TiO2 nanoparticles - Zeininger, Lukas; Lodermeyer, Fabian; Costa Riquelme, Rubén Dario; Guldi, Dirk Michael; Hirsch, Andreas (Chemical Communications, 2016)
We report on the orthogonal, highly directional and reversible self-assembly of porphyrins onto TiO2 nanoparticles by means of hydrogen bonding interactions. Unifying the stable covalent surface attachment of tailored, synthesized Hamilton receptors with the advantages of a non-covalent supramolecular immobilization of porphyrin cyanurates resulted in a redox- and photo-active nanohybrid. The latter was successfully implemented into a new type of supramolecular dye-sensitized solar cells.

Implementation of Single-Walled Carbon Nanohorns into Solar Cell Schemes - Lodermeyer, Fabian; Costa, Ruben Dario; Guldi, Dirk Michael (Advanced Energy Materials, 2017)
Recent advances in dye-sensitized solar cells (DSSC), including the use of nanocarbons, resulted in breakthroughs relevant to both the academic and industrial sectors. Their relevance encompasses, on one hand, the development and integration of novel nanocarbon/dye hybrids for superior light-harvesting and improved charge injection properties and, on the other hand, the integration of nanocarbons into each part of DSSCs for enhancing the charge collection efficiency as well as the dye and electrolyte regeneration processes. In the context of the earlier, control over the electron injection and recombination rates is realized on the molecular level. In the context of the latter, i) the charge transport and charge collection efficiencies in the photoelectrode are increased, ii) the charge recombination processes are reduced, when used as a nanocarbon-based buffer layer, iii) the ion diffusion and catalytic effects into (quasi) solid-state electrolytes are improved, and iv) devices using Pt-free counter electrodes with similar device efficiencies are realized. Leading examples of nanocarbons are graphene, carbon black, multi-walled carbon nanotubes, and single-walled carbon nanotubes. In this review, the focus is on a novel carbon allotrope, namely single-walled carbon nanohorns (SWCNH), which is discussed in depth and in comparison with other nanocarbons.
EAM Import::2019-03-13

N-Heterotriangulene chromophores with 4-pyridyl anchors for dye-sensitized solar cells - Meinhardt, Ute; Lodermeyer, Fabian; Schaub, Tobias; Kunzmann, Andreas; Dral, Pavlo O.; Sale, Anna Chiara; Hampel, Frank; Guldi, Dirk Michael; Costa, Ruben Dario; Kivala, Milan (RSC Advances, 2016)
A series of dimethylmethylene-bridged N-heterotriangulenes decorated with one, two, and three electron-withdrawing 4-pyridyls were synthesized. Their photophysical and electrochemical characteristics were examined and their successful application in n-type TiO2- and ZnO-based dye-sensitized solar cells demonstrated the ability of the 4-pyridyl moiety to act as an anchor.
EAM Import::2019-03-12

Novel nanographene/porphyrin hybrids-preparation, characterization, and application in solar energy conversion schemes - Kießling, Daniel; Costa, Ruben Dario; Katsukis, Georgios; Malig, Jenny; Lodermeyer, Fabian; Feihl, Sebastian; Roth, Alexandra Marina; Wibmer, Leonie; Kehrer, Matthias; Volland, Michel; Wagner, Pawel; Wallace, Gordon G.; et al. (Chemical Science, 2013)
Four novel nanographene/porphyrin hybrids were prepared, characterized, and probed in solar energy conversion schemes. Exfoliation of graphite by means of immobilizing four different porphyrins onto the basal plane of graphene is accompanied by distinct electronic interactions in both the ground and the excited states. In the ground state, a strong loss in oscillator strength goes hand-in-hand with a notable broadening of the porphyrin transitions and, as such, attests to the shift of electron density from the electron donating porphyrins to nanographene. In the excited state, a nearly quantitative quenching of the porphyrin fluorescence is indicative of full charge transfer. The latter is corroborated by femtosecond transient absorption measurements, which reveal the generation of the one-electron oxidized radical cation of the porphyrins with absorption maxima at 490 and 625 nm in the visible region and conduction band electrons in nanographene with features at 890 and 1025 nm in the near infrared region. We have demonstrated the applicability of the new nanographene/porphyrin hybrids in, for example, solar cells. In this regard, the presence of flakes is crucial in terms of influencing the injection processes, preventing aggregation, and reducing recombination losses, which are commonly encountered in porphyrin-based DSSCs. © 2013 The Royal Society of Chemistry.

Recent advances in multifunctional nanocarbons used in dye-sensitized solar cells - Costa Riquelme, Rubén Dario; Lodermeyer, Fabian; Casillas Pacheco, Ruben; Guldi, Dirk Michael (Energy and Environmental Science, 2014)
Throughout recent years the implementation of nanocarbons into dye-sensitized solar cells (DSSC) has resulted in important breakthroughs. The most relevant of them in this context are (i) the enhancement of charge transport and charge collection in nanocarbon-doped electrodes, (ii) the introduction of nanocarbon interlayers that simultaneously reduce the charge recombination and increase the charge collection efficiency, (iii) the use of nanocarbon-based, iodine-free, solid-state electrolytes featuring excellent diffusion coefficients and catalytic efficiencies, (iv) the use of novel nanocarbon-based hybrid dyes, and (v) the use of nanocarbons towards platinum-free counter electrodes. The first four aforementioned aspects are thoroughly described in this review. This journal is © the Partner Organisations 2014.

Review - Single-Walled Carbon Nanohorn-Based Dye-Sensitized Solar Cells - Lodermeyer, Fabian; Costa, Ruben Dario; Guldi, Dirk Michael (ECS Journal of Solid State Science and Technology, 2017)
Efforts in the broad field of dye-sensitized solar cells (DSSC) are governed by four key challenges: i) the development of photoelectrodes with high charge injection yields and charge collection efficiencies, ii) the development of low-cost buffer layers, which effectively reduce the back reaction of electrons from the transparent conductive oxide (TCO) to the electrolyte, iii) the design of platinum-free counter electrodes (CE), which feature good electrolyte regeneration yields, and iv) the implementation of (quasi) solid-state and iodine-free electrolytes featuring excellent ionic diffusion and conductivity. The introduction of nanocarbons into each component of DSSCs has emerged as a promising strategy to tackle all the aforementioned challenges. Leading examples of nanocarbons are graphene, carbon black (CB), multi-walled carbon nanotubes (MWCNT), and single-walled carbon nanotubes (SWCNT). Here, we focus on single-walled carbon nanohorns (SWCNH), which were successfully integrated into each of the aforementioned parts of DSSCs.
EAM Import::2019-03-13

Substituting TiCl4-Carbon Nanohorn Interfaces for Dye-Sensitized Solar Cells - Casillas Pacheco, Ruben; Lodermeyer, Fabian; Costa, Ruben Dario; Prato, Maurizio; Guldi, Dirk Michael (Advanced Energy Materials, 2013)
An easy-to-implement strategy to introduce carbon nanohorns as interlayers in the photoelectrode of a dye-sensitized solar cell without affecting its overall performance is presented. This provides a clean, easy, and ecofriendly alternative to achieve highly efficient cells.

Using carbon nanodots as inexpensive and environmentally friendly sensitizers in mesoscopic solar cells - Margraf, Johannes; Lodermeyer, Fabian; Strauß, Volker; Haines, Philipp; Walter, Johannes; Peukert, Wolfgang; Costa, Ruben Dario; Clark, Timothy; Guldi, Dirk Michael (Nanoscale Horizons, 2016)
We discuss the use of carbon nanodots (CNDs) as sensitizers in mesoscopic solar cells. The CNDs are synthesized using a one-step, bottom-up microwave approach with citric acid, urea, and formic acid as precursors in aqueous media. Their light-harvesting capabilities can be tuned by adjusting the synthetic parameters. Comprehensive spectroscopic and theoretical studies allow us to rationalize the nature of their absorption features. Promising power conversion efficiencies ( extgreekh) of 0.24% can be achieved from these cheap and eco-friendly sensitizers by optimizing the solar-cell assembly process. Interestingly, we found that extending the light absorption towards longer wavelengths does not necessarily improve the performance of the solar cells, since the longer-wavelength absorption features hardly contribute to the cells' photo-action spectra, so that the overall power conversion efficiency is actually worse. The origin of the lower performance is corroborated in transient absorption spectroscopy and photovoltage decay measurements. Our work points, on one hand, to the limits of as-synthesized CNDs as photosensitizers and, on the other hand, to possible improvements.